A Study Of Politeness Strategy In Refusal Used By English Teachers In Madiun Regency - Hartuti, Maya, Dr.Anam Sutopo, M.Hum (2014)
The study investigated politeness strategy in refusal conducted by the English teachers in Madiun regency relating to different social status levels and gender. The data were elicited, using discourse completion tasks (DCT), from 38 English teachers, 14 male and 24 female who teach in Junior high schools in Madiun regency. The collected data are analyzed by using Brown and Levinson's theory of politeness strategy. The refusal strategies were classified based on modified refusal taxonomy by Beebe et al. (1990). The findings of the research are described in line with the problem statements as follows: first, The English teachers of junior high school in Madiun regency applied two semantic formulae indirect and direct strategies in conjunction to adjunct identified by Beebe et al. (1990) across three refusals acts (invitations, offers and suggestions). The indirect strategy was the prominent refusal strategy especially in declining offers and suggestions where as the direct strategy was the highest strategy used in declining invitations. The second, the English teachers used all four politeness strategies (BOR, positive politeness (PP), NP, and OR) of Brown and Levinson (1987) across three refusals acts in more or lessthe same frequency, except in declining offers they did not use OR strategy. In declining invitations and suggestions, most of the English teachers applied PP strategy and the dominant type was PP 13 Give reasons. The dominant strategy in declining offers was BOR which most of them expressed gratitude. The third, the influence of social distance on politeness strategy used by the English teachers in declining invitations, offers, and suggestions was not significant. The most prevalent strategy in declining three acts of refusals across status levels was PP strategy. PP strategy mostly dominated the refusals to collocutors of equal and lower status but in refusals to collocutors of higher status, most of English teachers used NP strategy. The last, gender differences virtually has no influence on the choices of politeness strategy in three refusals acts across status levels. Both male and female English teachers conducted the same politeness strategies of Brown and Levinson (1987) in declining invitations, offers, and suggestions in more or less the same frequency. They used PP significantly the highest and OR was the least dominant strategy. Females used PP and NPlittle bit more often than males but males used BOR and OR little bit more often than females.